Electrophotographic belt and electrophotographic image forming apparatus
By incorporating a second polyester resin and carboxyl-containing acrylic resin in the hard coat layer of the electrophotographic belt, the adhesion and scratch resistance issues are addressed, enabling the production of high-quality images even under high curvature conditions.
Patent Information
- Application Number
- JP2020174428
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-18
- Filing Date
- 2020-10-16
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2040-10-16
AI Technical Summary
Existing electrophotographic belts face challenges with the adhesion of the hard coat layer to the base layer, especially when subjected to high curvature, leading to potential peeling issues.
The electrophotographic belt is designed with a laminated structure where the base layer contains a first polyester resin, and the hard coat layer comprises a second polyester resin and an acrylic resin with carboxyl groups, ensuring improved adhesion and scratch resistance.
This configuration results in an electrophotographic belt with enhanced scratch resistance and excellent layer adhesion, capable of stably forming high-quality electrophotographic images even under high curvature conditions.
Smart Images

Figure 0007669135000005 
Figure 0007669135000006 
Figure 0007669135000007
Abstract
Description
[Technical field]
[0001] The present disclosure is directed to an electrophotographic belt used in an electrophotographic image forming apparatus (hereinafter referred to as an "electrophotographic apparatus") such as a copying machine or a printer, and to an electrophotographic image forming apparatus. [Background technology]
[0002] In an electrophotographic image forming apparatus (hereinafter also referred to as an "electrophotographic apparatus"), an electrostatic image carrier such as a photosensitive drum is charged, and the charged electrostatic image carrier is exposed to light to form an electrostatic latent image. The electrostatic latent image is then developed with frictionally charged toner, and the toner image is transferred and fixed to a recording medium such as paper, thereby forming a desired image on the recording medium. A known transfer method for electrophotographic apparatuses is an intermediate transfer method in which an unfixed toner image on an electrostatic image carrier such as a photosensitive drum is primarily transferred to an intermediate transfer body by a current supplied from a transfer power source, and then the unfixed toner image is secondarily transferred from the intermediate transfer body to a recording medium.
[0003] Patent Documents 1 and 2 disclose, as an electrophotographic belt usable for an intermediate transfer body, an electrophotographic belt having a laminated structure in which a layer containing a thermoplastic resin (hereinafter also referred to as a "base layer" or a "first layer") and a layer containing an acrylic resin having a higher hardness than the base layer (hereinafter also referred to as a hard coat layer) are provided on the outer peripheral surface or inner peripheral surface of the base layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-330692 A [Patent Document 2] JP 2007-178750 A Summary of the Invention [Problem to be solved by the invention]
[0005] According to the study by the present inventors, the electrophotographic belts according to Patent Documents 1 and 2 still have room for improvement in the adhesion of the hard coat layer to the base layer. In particular, with the recent miniaturization of the main body of an electrophotographic device, the electrophotographic belt has come to be disposed in the electrophotographic device in a state where it is bent at a higher curvature. Therefore, the present inventors have recognized that it is necessary to develop a technology for obtaining an electrophotographic belt that can effectively prevent the hard coat layer from peeling off from the base layer even when it is bent at a higher curvature.
[0006] At least one aspect of the present disclosure is directed to providing an electrophotographic belt having excellent scratch resistance and excellent adhesion between layers.
[0007] At least one other aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images. [Means for solving the problem]
[0008] According to at least one embodiment of the present disclosure, a first layer; a second layer directly covering either an inner circumferential surface or an outer circumferential surface of the first layer, the first layer comprises a first polyester resin; The second layer of the electrophotographic belt includes a second polyester resin and an acrylic resin having a carboxyl group in the molecule.
[0009] According to at least one other aspect of the present disclosure, there is provided an electrophotographic image forming apparatus including a plurality of toner image carriers and an intermediate transfer belt onto which a toner image is primarily transferred from each of the plurality of toner image carriers, the intermediate transfer belt being the electrophotographic belt described above. Effect of the Invention
[0010] According to at least one aspect of the present disclosure, it is possible to obtain an electrophotographic belt having a laminated structure excellent in scratch resistance and excellent adhesion between layers, and according to at least one other aspect of the present disclosure, it is possible to obtain an electrophotographic image forming apparatus capable of stably forming high-quality electrophotographic images. [Brief description of the drawings]
[0011] [Figure 1] 1 is a schematic diagram of an electrophotographic belt according to one embodiment of the present disclosure, (a) is a perspective view of an electrophotographic belt having an endless shape, (b) is an enlarged view of a cross section in the thickness direction of an electrophotographic belt according to one embodiment of the present disclosure, and (c) is an enlarged view of a cross section in the thickness direction of an electrophotographic belt according to another embodiment of the present disclosure. [Diagram 2] 2 is a schematic diagram of an electrophotographic image forming apparatus according to another embodiment of the present disclosure. [Diagram 3] 3 is an enlarged schematic view of an image forming unit 205a in FIG. 2. FIG. [Figure 4] 1 is a schematic diagram illustrating a configuration of an outer circumferential surface of an electrophotographic belt according to an embodiment of the present disclosure. [Diagram 5] FIG. 2 is a schematic diagram showing the configuration of an imprint processing device for forming grooves on the surface of an electrophotographic belt. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In order to improve the adhesion of the hard coat layer to the base layer, the present inventors tried to incorporate a polyester resin as a binder resin in the base layer and also incorporate a polyester resin into the hard coat layer containing an acrylic resin. The intention was to incorporate a polyester resin into both the base layer and the hard coat layer to increase the affinity between the base layer and the hard coat layer, thereby improving the adhesion of the hard coat layer to the base layer. As a result, the adhesion of the hard coat layer to the base layer could be improved. On the other hand, the addition of the polyester resin to the hard coat layer reduced the scratch resistance of the hard coat layer.
[0013] Therefore, the present inventors have further studied to alleviate the deterioration of scratch resistance caused by the addition of a polyester resin to the hard coat layer, and have found that the deterioration of scratch resistance caused by the addition of a polyester resin to the hard coat layer can be suppressed by introducing a carboxyl group into the molecule of the acrylic resin in the hard coat layer.
[0014] That is, in an electrophotographic belt having a base layer (hereinafter also referred to as the "first layer") containing a first polyester resin as a binder resin, and a hard coat layer (hereinafter also referred to as the "second layer") containing an acrylic resin that directly covers at least one of the front and back surfaces of the first layer, by containing the second polyester resin and the acrylic resin having a carboxyl group in the molecule in the hard coat layer, it is possible to improve the adhesion of the second layer to the first layer while suppressing a decrease in the scratch resistance of the second layer.
[0015] Here, when a carboxyl group is present in the molecule of the acrylic resin in the second layer, the scratch resistance of the second layer is less likely to decrease even when the second polyester resin is present in the second layer. This is thought to be because an interaction similar to a hydrogen bond occurs between the terminal hydroxyl group of the second polyester resin and the carboxyl group of the acrylic resin, resulting in the formation of a pseudo-crosslinked structure between the acrylic resin and the second polyester resin.
[0016] The ratio of the hydroxyl groups of the second polyester resin to the carboxyl groups of the acrylic resin in the second layer (carboxyl groups / hydroxyl groups) is preferably 1.0 or more and 12.0 or less, particularly preferably 1.2 or more and 12.0 or less. By setting the ratio of the carboxyl groups to the hydroxyl groups within such a numerical range, the pseudo crosslinked structure described above can be more reliably formed in the second layer, and the decrease in scratch resistance of the second layer caused by the inclusion of the polyester resin in the second layer can be more effectively alleviated.
[0017] <Electrophotographic belts> An electrophotographic belt having an endless shape according to at least one embodiment of the present disclosure will be described in detail below with reference to Fig. 1(a) and Fig. 1(b). Fig. 1(a) is a perspective view of the electrophotographic belt 100.
[0018] Fig. 1(b) is an enlarged view of the axial cross section of Fig. 1(a). In the electrophotographic belt 100, the second layer 102 exists on the inner peripheral surface of the base layer 101, and the second layer is exposed to the inner peripheral surface of the electrophotographic belt. Although not shown, a third layer that comes into contact with a photosensitive drum or other members may be provided on the outer peripheral surface of the base layer.
[0019] By connecting a voltage maintaining element such as a Zener diode to the second layer via a member in contact with the second layer, it is possible to keep the potential of the second layer constant.
[0020] As a result, a desired current can be applied to all of the photosensitive drums via the second layer, and an electrophotographic belt can be provided that can be used in an image forming apparatus capable of performing not only secondary transfer but also primary transfer with one transfer power source as described in Patent Document 2.
[0021] The electrophotographic belt has an endless shape because it is used by being stretched over a plurality of rollers. The endless shape refers to a shape that can be stretched over a plurality of rollers and rotated. Among the endless shapes, a seamless shape without a joint (seam) is preferable from the viewpoint of reducing unevenness in the thickness of the belt. The electrophotographic belt having such a shape can be formed, for example, by a method of joining a sheet or film-shaped molded product into a cylindrical shape, or a method of extruding a resin material into a cylindrical shape.
[0022] The electrophotographic belt is used in the above-mentioned compact and low-cost image forming apparatus, and has a volume resistivity of 1×10 when 250 V is applied, measured in a standard environment (temperature 23° C., humidity 50%). 9 Ω cm or more 1×10 11In addition, the surface resistivity of the inner peripheral surface side is preferably smaller than that of the outer peripheral surface side, and the surface resistivity measured from the inner peripheral surface side is preferably within a range of 4.0×10 6 It is preferable that the surface resistivity is Ω / □ or less. By having such a surface resistivity, it is possible to make it more difficult for image defects such as transfer defects caused by insufficient transfer voltage required for the primary transfer of the toner image on the outer surface of the photosensitive drum to the transfer belt to occur.
[0023] Next, an example of the materials constituting each layer of the electrophotographic belt and a manufacturing method thereof will be described below, but the manufacturing method of the electrophotographic belt is not limited to the following example.
[0024] [Base layer (first layer)] The base layer contains a polyester resin (first polyester resin) as a binder resin.
[0025] Examples of such a base layer include a cylindrically connected semiconductive film in which a conductive agent is impregnated in a resin containing the first polyester resin, and a cylindrical seamless layer.
[0026] (First polyester resin) The first polyester resin can be obtained by polycondensation of a dicarboxylic acid component and a dihydroxy component, polycondensation of an oxycarboxylic acid component or a lactone component, or polycondensation using a plurality of these components, etc. The polyester resin may be a homopolyester or a copolyester.
[0027] Examples of the dicarboxylic acid component include aromatic dicarboxylic acids, alicyclic dicarboxylic acids, aliphatic dicarboxylic acids, and derivatives of these dicarboxylic acids. Examples of the aromatic dicarboxylic acids include those having 8 to 16 carbon atoms in the molecule (C8 to C16). Specific examples include terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acids such as 2,6-naphthalenedicarboxylic acid, diphenyldicarboxylic acid, diphenyletherdicarboxylic acid, diphenylmethanedicarboxylic acid, and diphenylethanedicarboxylic acid. Examples of the alicyclic dicarboxylic acids include C4 to C10 cycloalkanedicarboxylic acids such as cyclohexanedicarboxylic acid. Examples of the aliphatic dicarboxylic acids include C4 to C12 aliphatic dicarboxylic acids such as succinic acid, adipic acid, azelaic acid, and sebacic acid. Examples of the derivatives of these dicarboxylic acids include derivatives capable of forming esters (for example, lower alkyl esters such as dimethyl esters, acid anhydrides, and acid halides such as acid chlorides). These dicarboxylic acid components can be used alone or in combination of two or more. From the viewpoints of crystallinity and heat resistance, the dicarboxylic acid component is preferably an aromatic dicarboxylic acid, and more preferably terephthalic acid, isophthalic acid, or naphthalenedicarboxylic acid.
[0028] Examples of the dihydroxy component include aliphatic diols, alicyclic diols, and aromatic diols. Examples of the aliphatic diols include C2-C10 alkylene diols such as ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, and hexanediol. Examples of the alicyclic diols include C4-C12 alicyclic diols such as cyclohexanediol and cyclohexanedimethanol. Examples of the aromatic diols include C6-C20 ones such as hydroquinone, resorcin, dihydroxybiphenyl, naphthalenediol, dihydroxydiphenyl ether, and 2,2-bis(4-hydroxyphenyl)propane (bisphenol A). Other examples include alkylene oxide adducts of the aromatic diols (for example, C2-C4 alkylene oxide adducts of bisphenol A). Other examples include polyoxyalkylene glycols (e.g., polyoxy C2-C4 alkylene glycols such as diethylene glycol, polyoxyethylene glycol, polyoxypropylene glycol, and polytetramethylene ether glycol). These dihydroxy components may be derivatives capable of forming esters (e.g., alkyl groups, alkoxy groups, or halogen-substituted products). These dihydroxy components may be used alone or in combination of two or more. Among these dihydroxy components, it is preferable to use alkylene diols (particularly C2-C4 alkylene diols) and alicyclic diols from the viewpoints of crystallinity, heat resistance, and the like.
[0029] Examples of the oxycarboxylic acid component include the following: oxycarboxylic acids such as oxybenzoic acid, oxynaphthoic acid, diphenyleneoxycarboxylic acid, and 2-hydroxypropanoic acid, and derivatives of these oxycarboxylic acids. These oxycarboxylic acid components can be used alone or in combination of two or more.
[0030] The lactone component includes C3 to C12 lactones such as propiolactone, butyrolactone, valerolactone, caprolactone (for example, ε-caprolactone, etc.), etc. These lactone components can also be used alone or in combination of two or more.
[0031] Furthermore, a polyfunctional monomer may be used in combination within the range in which crystallinity and heat resistance are maintained.
[0032] Examples of polyfunctional monomers include polycarboxylic acids such as trimellitic acid, trimesic acid, and pyromellitic acid, and polyhydric alcohols such as glycerin, trimethylolpropane, trimethylolethane, and pentaerythritol. Polyesters having a branched or crosslinked structure produced by using such polyfunctional monomers can also be used.
[0033] The first polyester resin may be a polyester resin obtained by polycondensing the above components (dicarboxylic acid component and dihydroxy component, oxycarboxylic acid component, lactone component, or a plurality of these components). From the viewpoint of crystallinity, heat resistance, etc., at least one selected from polyalkylene terephthalate, polyalkylene naphthalate, and block / random copolymer of polyalkylene terephthalate and polyalkylene isophthalate is preferred. Examples of the copolymer include block copolymers and random copolymers. From the viewpoint of crystallinity and heat resistance, the number of carbon atoms of alkylene in polyalkylene terephthalate, polyalkylene isophthalate, and polyalkylene naphthalate is preferably 2 or more and 16 or less. More preferred is at least one selected from polyethylene terephthalate, block / random copolymer of polyethylene terephthalate and polyethylene isophthalate, and polyethylene naphthalate.
[0034] The first polyester resin may be a blend or alloy of two or more types.
[0035] Specific examples of polyethylene naphthalate include commercially available TN-8050SC (product name: manufactured by Teijin Ltd.) and TN-8065S (product name: manufactured by Teijin Ltd.). Specific examples of polyethylene terephthalate include commercially available TR-8550 (product name: manufactured by Teijin Ltd.), and specific examples of a copolymer of polyethylene terephthalate and polyethylene isophthalate include commercially available PIFG30 (product name: manufactured by Bell Polyester Products Co., Ltd.).
[0036] The intrinsic viscosity of the first polyester resin is preferably 1.4 dl / g or less, more preferably 0.3 dl / g to 1.2 dl / g, and even more preferably 0.4 dl / g to 1.1 dl / g. If the intrinsic viscosity is 1.4 dl / g or less, it is possible to efficiently prevent the fluidity from decreasing during molding. If the intrinsic viscosity is 0.3 dl / g or more, it is possible to efficiently ensure strength and durability. The intrinsic viscosity of the polyester resin is a value measured by using o-chlorophenol as a diluting solvent for the polyester resin, setting the concentration of the o-chlorophenol solution of the polyester resin to 0.5 mass%, and setting the temperature at 25°C.
[0037] The first polyester resin is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, based on the total mass of the base layer. If it is 50% by mass or more, the durability of the electrophotographic belt can be efficiently prevented from decreasing.
[0038] (Conductive agent) In the base layer, a nonionic or ionic conductive agent can be used as the conductive agent.
[0039] As the conductive agent, polymer-type and low molecular-weight conductive agents can be used. For example, in the polymer-type, polyether ester amide, polyethylene oxide-epichlorohydrin, polyether ester, etc. can be used as a nonionic type. As the polymer-type ionic conductive agent, quaternary ammonium group-containing acrylate polymer can be used as a cationic type, and polystyrene sulfonic acid can be used as an anionic type. As the low molecular-weight conductive agent, derivatives containing ether groups and derivatives containing ether esters can be used as a nonionic type. As the low molecular-weight ionic conductive agent, primary to tertiary ammonium salts, quaternary ammonium salts and their derivatives can be used as cationic types, and carboxylates, sulfates, sulfonates, phosphates and their derivatives can be used as anionic types. These polymer-type or low molecular-weight conductive agents can be used alone or in combination of two or more kinds, and among them, quaternary ammonium salts, sulfonates, polyether ester amides, etc. are preferably used from the viewpoint of heat resistance and conductivity.
[0040] Furthermore, additives such as plasticizers, antioxidants, antidecomposition agents, crystallization regulators, roughness adjusters, crosslinking agents, pigments, fillers, and elastomers may be added to the base layer as required.
[0041] (Method of forming base layer) The base layer can be formed, for example, by the following method. When a thermoplastic resin is used as the resin, an ionic surfactant as a conductive agent, a resin, and an additive as necessary are mixed and melt-kneaded using a biaxial kneading device or the like to prepare semiconductive pellets. Next, the pellets are extruded into a sheet shape, a film shape, or a seamless belt shape by melt extrusion to obtain a semiconductive film. It can also be molded by heat pressing or injection molding, and the formed preform can be stretch-blown to obtain a semiconductive film. The thickness of the base layer is preferably 20 μm or more and 500 μm or less, more preferably 30 μm or more and 150 μm or less.
[0042] The electrical resistance of the base layer thus obtained was 1.0×10 volume resistivity at 250 V applied. 8 Ω cm or more 1.0×10 12 It is preferable that the surface resistivity is 1.0×10 8 Ω / □ or more 1.0×10 12 It is preferably Ω / □ or less. By controlling the electrical resistance within this semiconductive region, defects in transferred images due to insufficient transfer voltage caused by charge-up in a low humidity environment or during continuous driving can be suppressed.
[0043] [Second layer] The second layer contains a second polyester resin and an acrylic resin (hereinafter also referred to as a "binder resin"). The surface resistivity of the second layer when 10 V is applied at a temperature of 23° C. and a humidity of 50% is 4.0×10 6 Ω / □ or less is preferable, and 1.0×10 6 Ω / □ or less. The lower limit of the surface resistivity is not particularly limited. When the surface resistivity is within the range, a primary transfer current equivalent to that of a conventional primary transfer having multiple transfer power sources can be supplied to each photosensitive drum. The surface resistivity is a value measured by a method for measuring the surface resistivity of the second layer described later.
[0044] The thickness of the second layer is preferably 0.05 μm to 10 μm, more preferably 0.1 μm to 5 μm, from the viewpoint of flex resistance. In consideration of the thickness, the binder resin is preferably one that can be dissolved in a solvent and form a thin layer containing the binder resin or a thin layer containing the binder resin raw material.
[0045] The second layer preferably has an average hardness of 0.10 GPa or more in a region of 10 to 20% from the outermost surface in the thickness (film thickness) direction in a nanoindenter measurement method using a Berkovich type indenter, more preferably 0.15 GPa or more. The region of less than 10% of the film thickness of the second layer near the outermost surface is easily affected by the measurement environment, such as the vibration of the indenter. Moreover, the region of more than 20% of the film thickness of the second layer is easily affected by the base layer. Therefore, these regions are excluded and the average hardness in the region of 10 to 20% of the film thickness of the second layer is calculated. By setting the hardness of the second layer to 0.15 GPa or more as the average hardness in the region, even when images are continuously output, the occurrence of physical deterioration such as wear and tear due to friction with other sliding members (e.g., transfer rollers, etc.) mounted on the electrophotographic device can be suppressed. The upper limit of the average hardness in the region of the second layer is not particularly limited, but it is preferably 0.50 GPa or less, since it can suppress physical damage to the sliding member mounted in a general electrophotographic device. That is, the average hardness in the region of the second layer is more preferably 0.15 GPa or more and 0.50 GPa or less, and particularly preferably 0.20 GPa or more and 0.40 GPa or less. Examples of methods for improving the hardness include a method of increasing the molecular weight of the polyester resin and a method of adding a high-hardness filler or a crosslinking agent.
[0046] (Second polyester resin) The second polyester resin used in the second layer preferably contains at least an aromatic polyester resin from the viewpoint of strength. For example, polyester resins having monomer units derived from phthalic acid selected from the group consisting of terephthalic acid, orthophthalic acid, and isophthalic acid can be mentioned. Specifically, copolymers having ethylene terephthalate units and ethylene orthophthalate units, copolymers having ethylene terephthalate units and ethylene isophthalate units, etc., are included. Another example is a copolymer having ethylene orthophthalate units and ethylene isophthalate units. These copolymers may be either block or random copolymers. In addition, two or more types of copolymers may be used as a blend or alloy mixture. Furthermore, it is preferable that the second layer contains a mixture of multiple polyesters with different chemical structures, which increases the amorphousness and improves the adhesion to the base layer. The chemical structure of the polyester resin can be identified by extracting the polyester from the second layer by an appropriate means such as dissolving it in a solvent, isolating it, and using pyrolysis GC / MS, IR, NMR, and elemental analysis.
[0047] In addition to the second polyester resin, the second layer may contain other additives within a range that does not impair the effect of this embodiment. Specific examples include the following: molybdenum disulfide, boron nitride, silicon nitride, layered clay minerals, silicone particles, fluororesin particles, silicone oil, fluorine oil, perfluoropolyether, crystallization control agent, crosslinking agent, etc. The other additives may be used alone or in combination of two or more.
[0048] Among these, when a crosslinking agent such as diisocyanate is added together with the raw material of the second polyester resin, the first polyester resin becomes a polymer having a urethane bond in the molecule (polyester urethane resin). Second Using a polyester urethane resin instead of the polyester resin is preferable from the viewpoint of improving the hardness of the second layer.
[0049] The Tg (glass transition temperature) of the polyester resin used in the second layer is preferably higher than 60°C from the viewpoint of heat resistance. If it is lower than 60°C, the second layer may soften due to the temperature rise in the image forming apparatus during printing or continuous printing in a high-temperature environment, and may fuse with a contacting member such as a transfer roller, causing image defects. The Tg of the binder resin can be calculated by observing the endothermic peak or baseline shift during temperature rise using a differential scanning calorimeter (DSC) after separating the resin from the second layer. The hydroxyl value of the polyester resin used in the second layer will be described in detail in Evaluation 5 below.
[0050] The weight average molecular weight (Mw) of the polyester resin is not particularly limited, but is preferably within the range of 40,000 to 200,000. When the weight average molecular weight of the polyester resin is 40,000 or more, the hardness of the second layer is more easily exhibited. When the weight average molecular weight (Mw) of the polyester resin is 200,000 or less, the solubility in a solvent is good and the increase in viscosity of the coating material can be suppressed, so that the desired film thickness is more easily obtained.
[0051] (Acrylic resin) The acrylic resin used in the second layer has a carboxyl group in the molecule.
[0052] The acrylic resin may, for example, be an acrylic resin having a structural unit represented by the following structural formula (1).
[0053] [ka]
[0054] In structural formula (1), R1 to R3 each independently represent a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms.
[0055] In addition, a solvent-soluble polymer type is preferred, because this allows the second layer to be formed by applying a paint containing the acrylic resin and drying it.
[0056] Specific examples of such acrylic resins include acrylic resins having monomer units such as acrylate, methacrylate, methyl acrylate, methyl methacrylate, ethyl acrylate, and ethyl methacrylate, and having a carboxyl group in the molecule. These polymers may be either block or random copolymers. In addition, mixtures in which two or more types of copolymers are blended or alloyed may be used.
[0057] The acid value (mgKOH / g) of the acrylic resin having a carboxyl group is not particularly limited, but is preferably 70 mgKOH / g or more. By setting the acid value to 70 mgKOH / g or more, even when used in combination with a polyester resin in the second layer, the decrease in hardness can be suppressed and good scratch resistance can be imparted. The method for measuring the acid value will be described in detail in Evaluation 5 below.
[0058] The weight average molecular weight (Mw) of the acrylic resin is not particularly limited, but is preferably in the range of 5000 to 200000. When the weight average molecular weight of the acrylic resin is 5000 or more, the hardness of the second layer is more easily expressed. When the weight average molecular weight (Mw) of the acrylic resin is 200000 or less, the solubility in the solvent is good and the increase in viscosity of the paint can be suppressed, so that the desired film thickness is more easily obtained. As such an acrylic resin, for example, a solventless acrylic polymer commercially available as the "ARUFON UC-3000" series (product name, manufactured by Toa Gosei Co., Ltd.) can be used. Specifically, "ARUFON UC-3000" has an acid value of 74 mg KOH / g and Mw of 10,000; "ARUFON UC-3080" has an acid value of 230 mg KOH / g and Mw of 14,000; "ARUFON UC-3510" has an acid value of 70 mg KOH / g and Mw of 2,000; "ARUFON UC-5080" has an acid value of 170 mg KOH / g and Mw of 17,000; and "ARUFON UC-5022" has an acid value of 235 mg KOH / g and Mw of 14,000.
[0059] The content of the acrylic resin in the second layer is not particularly limited, but from the viewpoint of improving scratch resistance, it is preferably 3% by mass or more, particularly 5% by mass or more, relative to the second layer. Also, from the viewpoint of adhesion to the polyester resin of the first layer, it is preferably 25% by mass or less, particularly 20% by mass or less, relative to the second layer.
[0060] (Conductive particles) Specific examples of electronic conductive agents that may be contained in the second layer to adjust the conductivity of the second layer are given below.
[0061] Carbon black, graphite, carbon nanotubes (hereinafter also referred to as "CNT"), carbon microcoils, graphene, zinc oxide, zinc antimonate, tin oxide, ITO (tin-doped indium oxide), ATO (antimony-doped tin oxide), conductive polymers (e.g., polyaniline, polypyrrole, polythiophene).
[0062] Among these, "Ketjen Black" (registered trademark) is preferred due to its high electrical conductivity. The content of carbon black in the second layer is not particularly limited, but is preferably 6% by mass or more in terms of adjusting the surface resistivity to the above-mentioned level. In addition, from the viewpoint of more reliably suppressing deterioration of physical properties such as cracking and wear due to friction with other sliding members (e.g., transfer rollers, tension rollers, etc.), the content of carbon black in the second layer is preferably 15% by mass or less. That is, the content of carbon black in the second layer is preferably in the range of 6% by mass or more and 15% by mass or less, and more preferably in the range of 9% by mass or more and 13% by mass or less.
[0063] Here, the carbon black content can be determined from the amount of residue left after the second layer is thermally decomposed. Among the materials constituting the second layer, carbon black has the highest thermal decomposition temperature. Therefore, the second layer sample scraped off from the electrophotographic belt and weighed is treated in an air atmosphere at a temperature equal to or higher than the decomposition temperature of the binder resin and lower than the decomposition temperature of the carbon black using a thermogravimetric analyzer (TGA) to advance the thermal decomposition reaction. This allows the content to be calculated. As a specific condition, the temperature is raised to 500°C at a rate of 20°C / min, and then held for several hours to advance the thermal decomposition reaction of substances other than carbon black. The completion of the thermal decomposition reaction can be determined when the weight loss rate becomes 1% / hour or less. The carbon black content may also be calculated from the amount of carbon black added when the second layer is formed.
[0064] (Method of forming the second layer) The second polyester resin and the acrylic resin are preferably soluble in a solvent such as methyl ethyl ketone, methyl isobutyl ketone, or cyclohexanone, because the second layer can be formed by applying a coating material containing the polyester resin and the acrylic resin, which is advantageous in terms of cost.
[0065] Specifically, for example, the method for forming the second layer includes a step of applying a coating of paint for forming the second layer, the coating containing polyester resin, acrylic resin, a solvent for dissolving the resin, and carbon black, onto the surface of the base layer, and removing the solvent.
[0066] The polyester resin can be obtained by transesterification and polycondensation from raw materials such as dicarboxylic acid and diol, or a commercially available polyester resin-containing paint can be used. Furthermore, the paint for forming the second layer may contain additives such as a leveling agent as necessary. As the leveling agent, a known agent can be appropriately selected and used. The obtained paint for forming the second layer is applied to the inner or outer peripheral surface of the base layer by a coating means such as dip coating, spray coating, ring coating, or roll coating. Thereafter, the solvent is dried and removed, and the second layer can be formed as a coating film.
[0067] [Third Layer] For the purpose of adhesion with other contact members such as a photosensitive drum or a cleaning blade, and for the purpose of preventing blocking, etc., a third layer 103 may be provided so as to be in direct contact with the surface of the outer peripheral surface and the inner peripheral surface of the base layer that is not covered with the second layer (see FIG. 1(c)). The third layer may contain a resin. The resin is not particularly limited, but considering the thickness of the third layer, it is preferable that the resin is soluble in a solvent and can be formed into a thin layer. As the resin, for example, soluble polyimide, polyester resin, cured urethane resin, acrylic resin, etc. can be used alone or in combination. In addition, the third layer may be formed using the same paint as the paint for forming the second layer.
[0068] In addition to the resin, it is preferable to add filler particles or a lubricant as an additive to the third layer. Specific examples include the following. Alumina, titania, silica, zirconia, zinc oxide, zinc antimonate, tin oxide, ITO (tin-doped indium oxide), ATO (antimony-doped tin oxide), molybdenum disulfide, boron nitride, silicon nitride, layered clay minerals, etc. Other examples include silicone particles, fluororesin particles such as PTFE (polytetrafluoroethylene) particles, carbon black, graphite, carbon nanotubes, carbon microcoils, graphene, etc. Further examples include silicone oil, fluorine oil, perfluoropolyether, etc. Among these, PTFE particles are preferable from the viewpoint of reducing friction. These may be used alone or in combination of two or more.
[0069] When PTFE particles are used, the content of the PTFE particles in the third layer is preferably 5 parts by mass or more and 60 parts by mass or less, and more preferably 10 parts by mass or more and 50 parts by mass or less, relative to 100 parts by mass of the resin in the third layer. By setting the content of the PTFE particles within the above range, adhesion and blocking with other contact members can be prevented. In addition, a conductive agent, a curing agent, an antioxidant, an ultraviolet absorbing agent, a pH adjusting agent, a crosslinking agent, a pigment, etc. can also be added to the third layer as necessary.
[0070] Furthermore, the outer surface of the third layer opposite to the side facing the base layer preferably has grooves, which can reduce the contact area with a member that comes into contact with the outer surface, such as a cleaning blade (hereinafter also referred to as a "contact member"), and can further reduce the frictional resistance between the outer surface and the contact member.
[0071] The method for forming the groove is not particularly limited, and examples of the method that can be used include a method in which the inner peripheral surface of the electrophotographic belt having the third layer is supported by a core, and then the outer surface of the third layer is polished by rotating the belt in the circumferential direction while being brought into contact with a lapping film containing abrasive grains, or a method such as imprint processing in which a mold previously processed into a desired shape is brought into contact with the outer surface.
[0072] FIG. 4 illustrates an electrophotographic belt 400 having an endless configuration in accordance with at least one other embodiment of the present disclosure, in which the outer surface of the third layer has grooves.
[0073] The electrophotographic belt 400 has a plurality of grooves 401 formed on its outer circumferential surface.
[0074] Each of the grooves 401 is formed so as to intersect with a line that is assumed to extend in a direction perpendicular to the circumferential direction of the electrophotographic belt. More specifically, each of the grooves 401 is provided in the circumferential direction of the electrophotographic belt 400 and non-parallel to the circumferential direction. Here, the narrow angle θ that each of the grooves 401 makes with the circumferential direction is preferably greater than 0° and less than ±3°. More preferably, the angle θ is less than ±1°. When the angle that the grooves 401 make with the circumferential direction is 0°, that is, when the grooves 401 extend parallel to the circumferential direction of the electrophotographic belt, the portion of the cleaning blade that abuts against the region of the electrophotographic belt that is sandwiched between two adjacent grooves 401 (hereinafter, also referred to as a land portion) is fixed, and only that portion is worn, which may cause cleaning defects.
[0075] The outer peripheral surface of the electrophotographic belt has a first region having n grooves in a direction perpendicular to the circumferential direction. 402 and a second region having more than n grooves in a direction perpendicular to the circumferential direction. 403 In this case, the first region and the second region are alternately arranged in the circumferential direction. 401 The number n of grooves is not particularly limited as long as the toner cleaning can be performed stably, but it is preferable that the number n is 2,000 to 120,000. 401 The area of the cleaning blade that comes into contact with the portion where the cleaning blade is not applied is reduced, so that the cleaning blade and the electrophotographic belt 400 The frictional force between the grooves can be reduced. 401 The toner above can be transferred better.
[0076] The number of grooves in the second region is ( 2n-10 ) That's all, ( 2n+10 )When the number of grooves in the second region is 2n-10 or more, the location of the contact portion of the cleaning blade at the boundary between the first region and the second region can be stably changed.
[0077] Furthermore, if the number of grooves in the second region is 2n+10 or less, the toner on the grooves can be transferred more effectively.
[0078] There is no particular restriction on the spacing between adjacent grooves, but it is preferable that the spacing be approximately equal from the viewpoint of toner cleaning. By making the spacing uniform, localized wear of the blade can be suppressed.
[0079] The circumferential length of the second region is preferably 0.01 to 50 mm. Each of the grooves may be discontinuous in the circumferential direction, and the second region may include the end of each groove. When the circumferential length of the second region is 50 mm or less, the toner on the grooves can be transferred more efficiently.
[0080] The second region is an electrophotographic belt. 400 There is at least one on the surface of It is preferable that It is particularly preferable that there are 2 to 3 second regions in the circumferential direction. By having 2 to 3 second regions in the circumferential direction of the electrophotographic belt, the toner on the grooves can be transferred more efficiently.
[0081] groove 401 The depth of the groove is preferably 0.10 μm or more and less than 5.0 μm, and more preferably 0.20 μm or more and less than 2.0 μm. By setting the groove depth within the above range, the contact state of the cleaning blade with the electrophotographic belt can be stabilized for a long period of time. do.
[0082] From the viewpoint of cracking and bending resistance, the thickness of the third layer is preferably 0.05 μm or more and 10 μm or less, and more preferably 0.1 μm or more and 5 μm or less.
[0083] <Electrophotographic device> Next, a color electrophotographic apparatus according to an embodiment of the present disclosure, in which the electrophotographic belt according to an embodiment of the present disclosure is used as an intermediate transfer belt, will be described with reference to FIG.
[0084] The electrophotographic device includes an image forming unit 205a for forming a yellow image, an image forming unit 205b for forming a magenta image, an image forming unit 205c for forming a cyan image, and an image forming unit 205d for forming a black image. Each image forming unit includes a photosensitive drum 205-1 which is a toner image carrier for carrying a toner image on its surface, and each photosensitive drum is in contact with the outer peripheral surface of an intermediate transfer belt 200 which is an electrophotographic belt according to one embodiment of the disclosure.
[0085] The intermediate transfer belt 200 is supported by three rollers: a driving roller and secondary transfer opposing roller 201, and tension rollers 202 and 203. The driving roller and secondary transfer opposing roller 201 has a rubber layer with high friction resistance on its surface in order to drive the intermediate transfer belt 200. The rubber layer has a volume resistivity of 1.0×10 5 The driving roller 201 also forms a secondary transfer section with the secondary transfer roller 204 via the intermediate transfer belt 200. The tension roller 202 is provided with a rubber layer, and the rubber layer has a volume resistivity of 1.0×10 5 The secondary transfer roller 204 has a conductivity of Ω·cm or less. The tension roller 203 may be a metal roller. The secondary transfer roller 204 is pressed against the drive roller / secondary transfer counter roller 201 via the intermediate transfer belt 200. The secondary transfer roller 204 has a volume resistivity of 1.0×10 7 Ω cm or more 1.0×10 9 An elastic roller having a resistance of Ω·cm or less can be used. The tension rollers 202 and 203 and the secondary transfer roller 204 rotate in accordance with the rotation of the intermediate transfer belt 200.
[0086] The secondary transfer roller 204 is in contact with the outer circumferential surface of the intermediate transfer belt 200 except during the secondary transfer process. The power source 214 applies a voltage to the secondary transfer roller 204, thereby passing a current from the secondary transfer roller 204 through the intermediate transfer belt 200 to each of the photosensitive drums constituting the image forming unit, thereby primarily transferring the toner images carried by the photosensitive drums from the photosensitive drums to the intermediate transfer belt 200. That is, the secondary transfer roller 204 functions as a current supplying member that supplies a current to the intermediate transfer belt 200 when the toner images carried by the photosensitive drums are primarily transferred to the outer circumferential surface of the intermediate transfer belt 200. In this way, the electrophotographic device shares a primary transfer power source and a secondary transfer power source.
[0087] The electrophotographic apparatus will be described in detail below, taking the image forming unit 205a as an example.
[0088] FIG. 3 is an enlarged schematic diagram of the image forming unit 205a. The image forming unit 205a has a photosensitive drum 206a, which is an image carrier, and is rotated at a predetermined process speed. Around the photosensitive drum 206a, a charging roller 207a, which is a charging member, a developing member 209a containing toner 208a, and a drum cleaning member 210a are installed. Furthermore, around the photosensitive drum 206a, an exposure member 211a is installed between the charging roller 207a and the developing member 209a. The photosensitive drum 206a is charged by the charging roller 207a, and the charged electrostatic image carrier is exposed by the exposure member 211a to form an electrostatic latent image (toner image). Thereafter, the electrostatic latent image is developed by the toner 208a, which is frictionally charged, in the developing member 209a, and is transferred to the intermediate transfer belt 200, which is installed at a position opposite each image forming unit, by a primary transfer voltage (hereinafter referred to as "primary transfer").
[0089] Similarly, in the image forming units 205b, 205c, and 205d, primary transfer is performed in synchronization with the rotation of the intermediate transfer belt 200 to form a four-color toner composite image. At that time, it is preferable to have one or more metal rollers 212 as primary transfer opposing members between the image forming units 205b and 205c at positions opposing the image forming units via the intermediate transfer belt 200. By forming a primary transfer unit by the metal roller 212 that presses the intermediate transfer belt 200 against the opposing image forming unit, the primary transfer unit width (nip) can be made wide and stable.
[0090] A recording medium 213 such as paper is supplied to a position on the intermediate transfer belt 200 downstream of the position of the fourth image forming unit 205d. A secondary transfer roller 204 (secondary transfer member) is disposed at the same position. The gap formed by the intermediate transfer belt 200 and the secondary transfer roller 204 where the toner image on the intermediate transfer belt 200 is transferred to the recording medium and its vicinity are referred to as the secondary transfer unit. As shown in FIG. 2, the secondary transfer unit is preferably configured to include a nip between a driving roller / secondary transfer opposing roller 201 and the secondary transfer roller 204. When a non-image portion immediately before the toner composite image formed on the intermediate transfer belt 200 reaches the secondary transfer unit, a voltage of the opposite polarity to the toner is applied from a voltage source 214 that supplies a current to the secondary transfer roller 204. Then, when the recording medium 213 passes through the secondary transfer unit in the direction of the arrow Vf in FIG. 2, the four-color toner composite image on the intermediate transfer belt 200 is transferred to the recording medium 213 all at once. This transfer is called "secondary transfer." The recording medium 213 on which the secondary transfer has been performed is fixed in a fixing unit (not shown) to become a color image. Meanwhile, toner that has not been secondary transferred and remains on the intermediate transfer belt 200 is scraped off by a cleaning blade 215 that comes into contact with the belt surface on which the tension roller 202 is disposed at any time, and is collected in a waste toner box 216. In this way, the surface of the intermediate transfer belt 200 returns to its initial state.
[0091] The electrophotographic apparatus according to one embodiment of the present disclosure obtains from the voltage source 214 not only the transfer voltage required for the secondary transfer but also the transfer voltage required for the primary transfer. The intermediate transfer belt 200 has, for example, a second layer on the inner circumferential surface of the belt. As shown in FIG. 2, the metal roller 212 that contacts the inner circumferential surface of the intermediate transfer belt is connected to a Zener diode 217, which is a constant voltage element, and is grounded. Therefore, the voltage applied from the voltage source 214 makes the potential of the second layer of the intermediate transfer belt constant in the circumferential direction. As a result, the potential differences between the photosensitive drums and the intermediate transfer belt in each image forming section 205a, 205b, 205c, and 205d become approximately equal, and the currents flowing to each photosensitive drum also become approximately equal, making the primary transfer possible. Note that, since the resistance value of the recording medium itself changes due to environmental fluctuations such as temperature and humidity during image formation, it is preferable to change the secondary transfer voltage within a certain range.
[0092] In the electrophotographic device, even if the secondary transfer voltage fluctuates, for example, if the secondary transfer voltage rises, a current flows when the Zener potential is exceeded because the Zener diode 217 is connected. This allows the potential of the second layer to be kept constant, and the primary transferability can be stabilized. Specifically, it is preferable that the applied voltage of the voltage source 214 is 1000 to 3500 V and the Zener potential is 220 to 300 V. According to this embodiment, by having the above-mentioned transfer configuration, primary transfer and secondary transfer can be stably performed by one transfer power source. EXAMPLES
[0093] Examples and comparative examples will be described below.
[0094] In the following examples and comparative examples, the materials in the paint may be diluted or dispersed in a solvent, but the amount of each material used (parts by mass) refers to the amount of non-volatile matter, excluding the solvent (volatile matter), unless otherwise specified.
[0095] Table 1 lists the materials used in the second layers of electrophotographic belts Nos. 1 to 17 according to Examples 1 to 7, Comparative Examples 1 to 9, and Reference Example 1. Table 2 lists the evaluation results of electrophotographic belts Nos. 1 to 17.
[0096] [Example 1] (Formation of the base layer) The following materials were prepared as raw materials for forming the base layer.
[0097] Polyethylene naphthalate (product name: Teonex TN8050SC, manufactured by Teijin Limited) (hereinafter referred to as “PE(1)”) as a polyester resin.
[0098] A copolymer of polyethylene terephthalate and polyethylene isophthalate (product name: PIFG30; manufactured by Bell Polyester Products, Inc.) (hereinafter referred to as "PE(2)") Polyetheresteramide (product name: TPAE-10HP-10, manufactured by T&K TOKA Corporation) (hereinafter referred to as "PEEA").
[0099] Potassium perfluorobutanesulfonate (product name: F-Top KFBS, manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.) (hereinafter referred to as "KFBS").
[0100] The melting point of PE(1) was 262°C.
[0101] The above PE(1) / PE(2) / PEEA / KFBS were mixed in a ratio of 72 / 8 / 18 / 2 (mass%) and melt-kneaded at 290°C for 5 minutes using a twin-screw extruder (trade name: TEX30α, manufactured by Japan Steel Works, Ltd.) to obtain a resin mixture consisting of PE(1), PEEA and KFBS. The obtained resin mixture was pelletized using a cutter (trade name: Fan Cutter, manufactured by Hoshi Plastics Co., Ltd.) to obtain resin mixture pellets (pellet size = major axis 3 mm x minor axis 2 mm). The obtained pellets were dried at 140°C for 6 hours. Next, the dried pellets of the resin mixture were placed in the hopper of an injection molding device (trade name: SE180D, manufactured by Sumitomo Heavy Industries, Ltd.). Then, the cylinder temperature was set to 290°C, melted under screw stirring, and injection molded into a mold to produce a test tube-shaped preform. The obtained preform was placed in a blow molding machine, and in a blow mold kept at a mold temperature of 110°C, a stretch bar and air were used to blow mold the preform at a preform temperature of 155°C, an air pressure of 0.3 MPa, and a stretch bar speed of 1000 mm / s to obtain a blown bottle. Both ends of the blown bottle were cut to cut out an electrophotographic base layer in the shape of an endless belt. The thickness of the base layer was 70 μm.
[0102] (Preparation of polyester resin for second layer) 194 parts by mass of dimethyl terephthalate, 194 parts by mass of dimethyl isophthalate, 239 parts by mass of ethylene glycol, and 38 parts by mass of diethylene glycol were charged into an autoclave. Next, 0.2 parts by mass of tetrabutyl titanate was charged into the autoclave as a catalyst, and the transesterification reaction was allowed to proceed for 5 hours at 190 to 220 ° C. Then, the reaction system was depressurized to 0.67 kPa (5 mmHg) over 20 minutes, and the temperature was raised to 280 ° C. during this time. Further, a polycondensation reaction was carried out at 13.3 Pa (0.1 mmHg) and 280 ° C. for 60 minutes to obtain a polyester (1) having monomer units derived from isophthalic acid and terephthalic acid. From the measurement by DSC, the glass transition temperature of the obtained polyester (1) was 65 ° C.
[0103] (Formation of the second layer) The following materials were used to form the second layer.
[0104] As an acrylic resin, a commercially available product having a carboxyl group, "ARUFON UC-3000" (product name, acid value 74 mgKOH / g, weight average molecular weight Mw=10000, manufactured by Toa Gosei Co., Ltd.) (hereinafter, "acrylic resin") was used. resin 1"). The polyester (1) Carbon black (product name: MHI Black #273; manufactured by Mikuni Shikiso Co., Ltd.) (hereinafter referred to as "carbon")
[0105] The above acrylic resin (1) / polyester (1) / carbon were mixed in a ratio of 8.1 / 81.3 / 10.6 (mass%). The mixture obtained was diluted with methyl ethyl ketone so that the solid content concentration was 15 mass%, and stirred with a stirrer to obtain a uniform coating material for forming the second layer. This coating material was uniformly applied to the inner circumferential surface of the base layer by a spray method, and dried at 70°C for 5 minutes. As a result, electrophotographic belt No. 1 was obtained in which a second layer having a thickness of 2 μm was formed on the inner circumferential surface of the base layer. Then, electrophotographic belt No. 1 was subjected to the following evaluations 1 to 6.
[0106] <Evaluation 1. Measurement of the average hardness of the second layer> The hardness of the second layer was measured using a Berkovich type indenter with a microindentation hardness tester (product name: Nanoindenter G200, manufactured by Agilent Technologies). The measurement area was 10-20% of the second layer from the outermost surface in the thickness direction, and the average hardness in this area was calculated. The results are shown in Table 2. In Table 2, "N" indicates that the acrylic resin and polyester resin have undergone phase separation, resulting in a significantly uneven coating surface, and indicates that "evaluation is not possible."
[0107] <Evaluation 2. Resistivity measurement> The surface resistivity of the second layer was measured in accordance with Japan Industrial Standards (JIS) K 6911 using a resistivity meter (product name: Hiresta UP MCP-HT450 type, manufactured by Mitsubishi Chemical Analytech Co., Ltd.). The surface resistivity of the second layer was measured in an environment of 23° C. and 50% relative humidity by contacting a URSS probe with the second layer, applying a voltage of 10 V, and measuring for 10 seconds, and the measured values were taken as the measured values. The circumferential direction of the second layer was measured at four points every 90° phase, and the average of the measured values was calculated. The volume resistivity of the electrophotographic belt including the base layer and the second layer was measured in the above environment by contacting a UR probe from the outer peripheral surface side, applying a voltage of 250 V, and measuring for 10 seconds, and the measured values were taken as the measured values. The circumferential direction of the electrophotographic belt was measured at four points every 90° phase, and the average of the measured values was calculated. The results are shown in Table 2.
[0108] <Evaluation 3. Scratch resistance evaluation> A second layer was prepared in the same manner as above, except that the paint prepared in the examples and comparative examples was applied using a glass plate instead of the base layer. The scratch resistance of the second layer was evaluated by contacting steel wool (#0000) with the surface of the sample held on a reciprocating abrasion test stand, applying a load of 500 g, and reciprocating 50 times at a reciprocating speed of 10 cm / sec. Before and after the start of the test, the gloss was measured at an angle of 60° to the coating surface using a gloss meter (IG-320, manufactured by Horiba, Ltd.), and the percentage of the quotient of the gloss before the test to the gloss after the test was taken as the gloss retention rate, which was used as an index of scratch resistance. The measurement results were evaluated based on the following criteria.
[0109] Rank A (very good scratch resistance): Gloss retention rate is 75% or more Rank B (good scratch resistance): Gloss retention rate is 55% or more and less than 75% Rank C (poor scratch resistance): Gloss retention rate is less than 55%
[0110] <Evaluation 4. Adhesion evaluation> The transfer belts obtained in the examples and comparative examples were evaluated according to JIS K5400. A cutter was used to make incisions reaching the interface between the base layer and the second layer to create 100 1 mm x 1 mm grids, and adhesive tape (product name: cellophane tape; manufactured by Nichiban Co., Ltd.) was attached to the belts, which were then pulled at an angle of 90 degrees to peel off. The results were evaluated according to the following criteria.
[0111] Rank A (very good with no peeling observed) Rank B (very small peeling is observed at some of the intersections of the cuts, but it is still good) Rank C (Partial or complete peeling along the cut line)
[0112] <Evaluation 5. Measurement of acid value and hydroxyl value> The acid value of acrylic resin and the hydroxyl value of polyester resin are in accordance with the Japanese Industrial Standards (JIS) K007. 0 reference Finger By titration method Analysis, and Hydroxyl value titration analysis (Acetylation method) and calculated using the following formula (1) and formula (2). Calculation formula (1) Hydroxyl value (mgKOH / g) = {(V1-V0)×f1×0.5×56.11} / S1+acid value In the above formula (1), S1: Mass of sample (g) V0: Amount of 0.5 mol / L potassium hydroxide alcohol solution required in the blank test (mL) V1: Amount of 0.5 mol / L potassium hydroxide alcohol solution required in this test (mL) f1: Factor of 0.5 mol / L potassium hydroxide alcohol solution (1.005) It is. Calculation formula (2) Acid value (mgKOH / g)={(V3-V2)×f2×0.1×56.11} / S2 In the above formula (2), S2: Mass of sample (g) V2: Amount of 0.1 mol / L potassium hydroxide alcohol solution required in the blank test (mL) V3: Amount of 0.1 mol / L potassium hydroxide alcohol solution required in this test (mL) f2: The factor of 0.1 mol / L alcohol solution of potassium hydroxide (1.006).
[0113] The hydroxyl value titration analysis is described in detail below.
[0114] Add approximately 2 g of the sample to be measured and 5 mL of acetylation reagent to a 200 mL Erlenmeyer flask, then attach an air-cooled tube and react in a 100°C oil bath for 1 hour. Allow to cool at room temperature, then add 1 mL of water. Heat again in a 100°C oil bath for 10 minutes. After allowing to cool, rinse the inside of the air-cooled tube and the inner walls of the flask with ethanol. Dilute the solution with 30 mL of pyridine. Using a 1% phenolphthalein solution as an indicator, titrate with a 0.5 mol / L alcoholic solution of potassium hydroxide (f=1.005), and mark the end point as the point at which the solution turns light red.
[0115] A blank test is also carried out in the same manner, and the hydroxyl value is calculated from the above formula. Note that the acetylation reagent is prepared by weighing 20 g of acetic anhydride into a flask, and then adding pyridine to make 100 mL.
[0116] The acid value titration analysis is described in detail below.
[0117] Put 2g of sample, 30mL of ethanol, and 30mL of 2-butanone into a 100mL Erlenmeyer flask and dissolve at room temperature. Using 1% phenolphthalein solution as an indicator, titrate with 0.1mol / L potassium hydroxide alcohol solution (f=1.006), and the end point is when the solution turns red. A blank test is also performed in the same way, and the acid value is calculated using the above formula.
[0118] The calculated acid value and hydroxyl value were values per 1 g of the acrylic resin and polyester resin being measured, and these values were multiplied by the content of each resin shown in Table 1 to calculate the "carboxyl group / hydroxyl group" ratio.
[0119] Table 1 shows the acid value and hydroxyl value of the binder resin used in the second layer of the transfer belt according to each of the examples and comparative examples described below, based on the above evaluation 5.
[0120] <Evaluation 6. Image quality evaluation> The obtained electrophotographic belt was used as an intermediate transfer belt of an electrophotographic image forming apparatus having the configuration shown in FIG. 2 to form an electrophotographic image, and the presence or absence of image defects due to secondary transfer was observed. As the paper, letter-size (width 216 mm) plain paper (product name: Business 4200, Xerox Corporation, basis weight: 75 g / m 2 ) was used, and the print mode was a secondary color image created by superimposing two solid color toner images output in single-sided print mode.
[0121] Here, the secondary color image is an image with an average density of 200% for red (R), green (G), and blue (B), and 150,000 sheets were output, and the first sheet (hereinafter also referred to as "initial") and the 150,000th output image were evaluated. In addition, after the above number of sheets were output, the electrophotographic belt was removed from the image forming apparatus, and the surface of the second layer was visually observed. Then, the presence or absence of peeling of the second layer from the base layer and the occurrence of scratches was evaluated according to the following criteria.
[0122] Rank A: No peeling or scratches on the second layer from the base layer, and the output image is good. Rank C: Peeling or scratches on the second layer from the base layer were confirmed, and image defects occurred in the output image corresponding to the peeled or scratched areas due to belt unevenness. Rank N: Image defects occur due to insufficient transfer voltage.
[0123] [Example 2] An electrophotographic belt No. 2 was obtained in the same manner as in Example 1, except that the polyester (1) in the second layer of Example 1 was changed to a polyester urethane resin having monomer units derived from terephthalic acid and isophthalic acid (product name: Vylon UR1400; manufactured by Toyobo Co., Ltd.) (hereinafter referred to as "polyester (2)"). The glass transition temperature of the obtained polyester (2) was 83°C as measured by DSC. The obtained electrophotographic belt No. 2 was subjected to the above-mentioned evaluations 1 to 6.
[0124] [Example 3] An electrophotographic belt No. 3 was obtained in the same manner as in Example 2, except that the ratio of acrylic resin (1) / polyester (2) / carbon was changed to 14.9 / 74.5 / 10.6 (mass%) in Example 2. The obtained electrophotographic belt No. 3 was subjected to the above-mentioned evaluations 1 to 6.
[0125] [Example 4] Electrophotographic belt No. 1 was produced in the same manner as in Example 3, except that the ratio of acrylic resin (1) / polyester (2) / carbon was changed to 20.6 / 68.8 / 10.6 (mass%). 4 The obtained electrophotographic belt No. 4 were subjected to the above-mentioned evaluations 1 to 6.
[0126] [Example 5] Electrophotographic belt No. 5 was obtained in the same manner as in Example 1, except that the polyester (1) in the second layer of Example 1 was changed to a polyester urethane resin having monomer units derived from orthophthalic acid and isophthalic acid (product name: Vylon UR8200; manufactured by Toyobo Co., Ltd.) (hereinafter referred to as "polyester (3)"). The glass transition temperature of the obtained polyester (3) was 73°C as measured by DSC. The obtained electrophotographic belt No. 5 was subjected to the above-mentioned evaluations 1 to 6.
[0127] [Example 6] Electrophotographic belt No. 6 was obtained in the same manner as in Example 1, except that the polyester (1) in the second layer of Example 1 was changed to a polyester urethane resin having monomer units derived from terephthalic acid and isophthalic acid (product name: Vylon UR4800; manufactured by Toyobo Co., Ltd.) (hereinafter referred to as "polyester (4)"). The glass transition temperature of the obtained polyester (4) was 106°C as measured by DSC. The obtained electrophotographic belt No. 6 was subjected to the above-mentioned evaluations 1 to 6.
[0128] [Example 7] The same paint as the paint for forming the second layer was applied to the outer peripheral surface of the electrophotographic belt No. 1 obtained in Example 1 in the same manner as in Example 1 to prepare an electrophotographic belt 500 having a third layer formed thereon.
[0129] Using the imprint processing device shown in Fig. 5, grooves were formed in a prepared electrophotographic belt 500. A groove-imparting cylindrical mold 501 was prepared by cutting, having a diameter of 50 mm, a length of 250 mm, a convex height of 3.5 µm, a convex bottom length of 2.0 µm, a convex top length of 0.2 µm, and a convex pattern interval of 20 µm, with the convex patterns continuously formed in a spiral shape and an angle of 0.1° between the convex patterns of the groove-imparting cylindrical mold 501 and the circumferential direction of the convex patterns, and made of carbon steel (S45C) plated with electroless nickel. A cartridge heater was embedded in the groove-imparting cylindrical mold 501, allowing heating.
[0130] The electrophotographic belt 500 was fitted around the outer periphery of a cylindrical belt holding mold 503 (circumferential length 712 mm). Both the groove-imparting cylindrical mold 501 and the cylindrical belt holding mold 503 can rotate on their own axis. Both molds were rotated at 30 mm / sec (their rotation directions were opposite to each other), and while maintaining their axial centerlines parallel to each other, the groove-imparting cylindrical mold 501 heated to 130° C. was pressed against the cylindrical belt holding mold 503 with a pressure of 8.0 MPa. By this method, the convex pattern of the groove-imparting cylindrical mold 501 was transferred to the outer periphery of the electrophotographic belt 500, that is, the outer surface of the third layer. When the cylindrical belt holding mold 503 had slightly completed one revolution (corresponding to 1 mm), the groove-imparting cylindrical mold 501 was released from the outer surface of the electrophotographic belt 500. In this manner, an electrophotographic belt No. 7 having grooves on its outer periphery was obtained.
[0131] Since the convex pattern of the groove-imparting cylindrical die 501 was spiral-shaped, the start and end of the grooves did not connect when the groove-imparting cylindrical die rotated once during groove formation. Therefore, the outer surface of the electrophotographic belt No. 7 was composed of a first region having n grooves in a direction perpendicular to the circumferential direction, and a second region having more than n grooves. Specifically, the outer surface of the obtained electrophotographic belt No. 7 was composed of one first region and one second region. The number of grooves in the direction perpendicular to the circumferential direction in the first region was 12,200. The number of grooves in the direction perpendicular to the circumferential direction in the second region was 24,401. Furthermore, the circumferential length of the second region was 1.1 mm, and the narrow angle θ of each groove relative to the circumferential direction was 0.1°. The obtained electrophotographic belt No. 7 was subjected to the evaluations 1 to 6.
[0132] [Example 8] The paint for forming the third layer was prepared as follows.
[0133] That is, a mixture obtained by mixing acrylic resin (1) / polyester (1) in a ratio of 9.1 / 90.9 (mass%) was diluted with methyl ethyl ketone so that the solid content concentration became 15 mass%, and the mixture was stirred with a stirrer to prepare a coating material for forming a third layer.
[0134] A third layer forming coating material was uniformly applied by spraying to the outer peripheral surface of the base layer of the electrophotographic belt No. 1 obtained in Example 1 on the side opposite to the side on which the second layer was formed, and dried at a temperature of 70°C for 5 minutes. Thus, a third layer having a thickness of 2 μm was formed on the outer peripheral surface of the base layer. Next, a groove was formed on the outer surface of the third layer in the same manner as in Example 7 to obtain an electrophotographic belt No. 8. The obtained electrophotographic belt No. 8 was subjected to the above-mentioned evaluations 1 to 6. Evaluations 1 to 4 and evaluation 6 were also performed on the third layer in the same manner as the second layer.
[0135] [Comparative Example 1] Electrophotographic belt No. 9 was obtained in the same manner as in Example 1, except that acrylic (1) was not used and the ratio of polyester (1) / carbon was changed to 89.4 / 10.6 (mass%) in Example 1. The obtained electrophotographic belt No. 9 was subjected to the above-mentioned evaluations 1 to 6.
[0136] [Comparative Example 2] An electrophotographic belt No. 10 was obtained in the same manner as in Example 1, except that the acrylic (1) in Example 1 was changed to a non-functional acrylic resin (product name: ARUFONUP-1170; manufactured by Toa Gosei Co., Ltd.) (hereinafter referred to as "acrylic (2)") The obtained electrophotographic belt No. 10 was subjected to the above-mentioned evaluations 1 to 6.
[0137] [Comparative Example 3] The same procedure as in Comparative Example 3 was repeated except that the acrylic (2) was changed to an acrylic resin having a hydroxyl group (product name: ARUFON UH-2000; manufactured by Toa Gosei Co., Ltd.) (hereinafter referred to as "acrylic (3)"). 2 In the same manner as above, electrophotographic belt No. 11 was obtained. The obtained electrophotographic belt No. 11 was subjected to the above-mentioned evaluations 1 to 6.
[0138] [Comparative Example 4] An electrophotographic belt No. 12 was obtained in the same manner as in Example 1, except that the polyester (1) was not used and the ratio of acrylic (1) / carbon was changed to 89.4 / 10.6 (mass%) in Example 1. The obtained electrophotographic belt No. 12 was subjected to the above-mentioned evaluations 1 to 6.
[0139] [Comparative Example 5] Electrophotographic belt No. 13 was obtained in the same manner as in Comparative Example 2, except that polyester (1) was omitted and the ratio of acrylic (2) / carbon was changed to 89.4 / 10.6 (mass %) in Comparative Example 2. The obtained electrophotographic belt No. 13 was subjected to the above-mentioned evaluations 1 to 6.
[0140] The evaluation results are shown in Table 2.
[0141] [Table 1]
[0142] [Table 2]
[0143] The evaluation results shown in Table 2 are described below.
[0144] The electrophotographic belts No. 1 to 8 according to Examples 1 to 8, which contain a carboxyl group-containing acrylic resin and a polyester resin in the second layer, are excellent in both scratch resistance and interlayer adhesion, and the quality of the output image on the 150,000th sheet is also excellent.
[0145] When a carboxyl group is present in the molecule of the acrylic resin in the second layer, the scratch resistance of the second layer is unlikely to decrease even if a polyester resin is present in the second layer. This is thought to be because an interaction similar to a hydrogen bond occurs between the terminal hydroxyl group of the polyester resin and the carboxyl group of the acrylic resin, forming a pseudo-crosslinked structure between the acrylic resin and the polyester resin.
[0146] Furthermore, electrophotographic belts No. 2, No. 5, and No. 6 containing polyester resins having urethane groups (polyesters (2) to (4)) had higher hardness and were particularly good in scratch resistance compared to electrophotographic belt No. 1.
[0147] On the other hand, in electrophotographic belt No. 9 according to Comparative Example 1, which contains a polyester resin not having a carboxyl group-containing acrylic resin in the second layer, the adhesion was good, but the scratch resistance was not at a sufficient level, and in the output image of the 150,000th sheet, an image defect due to scratches occurring on the inner peripheral surface of the electrophotographic belt was confirmed. On the other hand, in electrophotographic belts No. 12 and No. 13, which do not contain a polyester resin in the second layer, the adhesion with the base layer was not at a sufficient level, and in the output image of the 150,000th sheet, an image defect due to unevenness caused by peeling of the second layer from the base layer occurring on the inner peripheral surface of the electrophotographic belt was confirmed.
Claims
1. An electrophotographic belt having a first layer which is a base layer and a second layer which directly covers an inner peripheral surface of the first layer, the first layer comprises a first polyester resin; The second layer comprises a second polyester resin and an acrylic resin having a carboxyl group in the molecule.
2. 2. The electrophotographic belt according to claim 1, wherein said first polyester resin is at least one of polyethylene terephthalate and polyethylene naphthalate.
3. 3. The electrophotographic belt according to claim 1, wherein the acrylic resin having a carboxyl group in the molecule contains a structural unit represented by the following formula (1): 【Chemistry 1】 [R in structural formula (1)] 1 ~R 3 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 3 carbon atoms.
4. 4. The electrophotographic belt according to claim 1, wherein the acrylic resin having a carboxyl group in the molecule has an acid value of 70 mgKOH / g or more.
5. 5. The electrophotographic belt according to claim 1, wherein the second polyester resin is a polyester urethane resin.
6. 6. The electrophotographic belt according to claim 1, wherein a content ratio of hydroxyl groups of the polyester resin and carboxyl groups of the acrylic resin contained in the second layer (carboxyl groups / hydroxyl groups) is 1.0 or more and 12.0 or less.
7. 7. The electrophotographic belt according to claim 1, wherein the electrophotographic belt has an endless shape.
8. 8. The electrophotographic belt according to claim 1, wherein the second layer has a thickness of 0.05 μm or more and 10 μm or less.
9. A third layer directly covering an outer circumferential surface of the first layer is further provided, 9. The electrophotographic belt according to claim 1, wherein the third layer has grooves on its outer surface.
10. 10. The electrophotographic belt according to claim 9, wherein said grooves are provided on the outer surface of said third layer so as to extend in a circumferential direction of said electrophotographic belt and to be non-parallel to said circumferential direction.
11. 11. The electrophotographic belt according to claim 1, wherein the hardness of the second layer measured on an outer surface thereof is 0.10 GPa or more in an area of 10 to 20% from the outermost surface in a thickness direction, as measured by a nanoindenter measurement method using a Berkovich type indenter.
12. The second layer contains conductive particles, and the surface resistivity of the second layer is 4.0×10 6 12. The electrophotographic belt according to claim 1, wherein the surface roughness is Ω / □ or less.
13. The electrophotographic belt has a volume resistivity of 1×10 9 Ω・cm or more 1×10 11 13. The electrophotographic belt according to claim 1, wherein the surface roughness is Ω·cm or less.
14. The electrophotographic belt according to claim 1, wherein the first layer has a thickness of 20 μm or more and 500 μm or less.
15. a plurality of toner image carriers; and an intermediate transfer belt onto which a toner image is primarily transferred from each of the plurality of toner image carriers; 15. An electrophotographic image forming apparatus, wherein the intermediate transfer belt is the electrophotographic belt according to claim 1.
16. the electrophotographic image forming apparatus further comprises a current supplying member in contact with the intermediate transfer belt, and a power source that applies a voltage to the current supplying member, 16. The electrophotographic image forming apparatus according to claim 15, wherein a voltage is applied from the power source to the current supply member to cause a current to flow in the circumferential direction of the intermediate transfer belt, thereby primarily transferring the toner image from the toner image carrier to the intermediate transfer belt.
17. 17. The electrophotographic image forming apparatus according to claim 16, wherein the current supplying member is in contact with an outer peripheral surface of the electrophotographic belt.
Citation Information
Patent Citations
Conductive endless belt, its manufacturing method, and image forming apparatus using same
JP2006184787A
Electrophotographic belt, electrophotographic apparatus, method for producing electrophotographic belt and intermediate transfer belt
JP2006330692A
Belt for image forming apparatus and image forming apparatus provided with same
JP2007178750A
Toner, and image forming method and process cartridge using the toner
JP2011197268A
Cylindrical member, transfer device, and image forming device
JP2013041121A